Effects of soil physicochemical properties on sweet corn quality in western Thailand - Trakoonyingcharoen, Punyisa; Kaewruang, Siraprapa; Phommuangkhuk, Aunthicha (Brawijaya University, 2025)
Thailand exports the greatest amount of sweet corn globally; however, its value per unit is low. Soil property knowledge can help to produce sweet corn with the best nutrition and taste qualities that could improve its value. This study investigated the association between soil properties and sweet corn qualitative attributes in western Thailand. Soils and sweet corn samples were taken from 8 soil series at 47 sites in the dry season. Disturbed and undisturbed soil samples were collected and analyzed using physicochemical methods. Five selected sweet corn samples were determined for pod weight without husk, ß carotene concentration, and total soluble solids. Principal component analysis with varimax rotation was used to determine the most important variables and patterns among the physicochemical properties. Three components with eigenvalues greater than 1 explained more than 66% of the total variance. The linear mixed model showed that ß carotene concentration and total soluble solids were linearly correlated with only one principal component factor (R2 = 56.6 and 64.6%, respectively), whereas there were no significant associations for total yield nor pod weight without husk with any of the principal component factors. Cluster analysis indicated that most of the soil sites were Oxyaquic Haplustalfs, Aeric Endoaqualfs, and Typic Haplustalfs with moderately well drained, and producing high-quality sweet corn. These findings should inform land use planning to improve the quality of sweet corn plantations in the dry season in western Thailand.